Episodes in the mathematics of medieval Islam - Berggren, J. L. (Springer, 2016)
This book presents an account of selected topics from key mathematical works of medieval Islam, based on the Arabic texts themselves. The author puts the works into their historical context and includes numerous examples of how mathematics interacted with Islamic society.